Effect of Helicobacter pylori eradication on peptic ulcer healing. - O'Connor, H. J. (BMJ Group, 1995)
In a prospective study designed to assess the effect of Helicobacter pylori eradication on peptic ulcer healing, 85 consecutive patients with H. pylori-positive peptic ulcer disease were treated with a triple therapy regimen consisting of colloidal bismuth subcitrate 120 mg four times daily for 28 days, with metronidazole 400 mg three times daily and tetracycline 500 mg three times daily for the first seven days of treatment. H. pylori status was assessed by CLO test and histology at least four weeks after completing therapy. Of 75 patients (88%) H. pylori-negative after therapy, 69 (92%) had healed ulcers compared with only five of 10 patients (50%) who remained H. pylori-positive (p = 0.003). Cigarette smoking had no significant effect on ulcer healing. Our results suggest that H. pylori eradication may accelerate ulcer healing and provide further evidence that an effective helicobactericidal regimen is the treatment of choice in H. pylori-positive peptic ulcer.